Sophocles’ Trachiniae and the Apotheosis of Herakles: The Importance of Acheloios and Some Numismatic Confirmations - Molinari, Dr Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2018)
Although the Trachiniae receives relatively little attention among commentators and is considered by many to be inferior to Sophocles’ other plays, I believe this lack of attention and regard results from a misunderstanding of the role of Acheloios in the play. The Trachiniae was probably written in the second half of the fifth century B.C.E., though we do not know precisely when. While I will offer no evidence about its dating (I follow Segal, so c. 430 B.C.E.), I will make it clear that Acheloios is essential to understanding the apotheosis of Herakles, and, moreover, we gain further insight about the mythos of Acheloios from Sophocles’ treatment. To do this, in Part I of this essay, I will review some of my earlier work (written with Dr. Nicola Sisci) that explains some important elements of the cult of Acheloios and its surrounding mythos. In Parts II-V, I will exhibit many passages from the Trachiniae and argue that they are directly related to the Acheloios tradition. In doing so, I will try to demonstrate that the connection of the apotheosis of Herakles to Acheloios is not just a creative interpretation on my part, but a clear, deliberate strategy employed by Sophocles to situate Acheloios in his role as psychopomp. Moreover, I will argue that a careful reading of the play reveals how Acheloios functions as the expiatory sacrifice necessary for Herakles’ transition to divinity, and that process involves the assimilation of Herakles with Acheloios. Part of this discussion will also involve the general notion of impiety as it relates to the cults of Acheloios and Kypris and how this impiety reinforces Herakles’ need for redemption as a prerequisite to apotheosis. Finally, in Part VI, I will examine some coins from Tarsos, in Cilicia, and show how two particular varieties reinforce my interpretation of Acheloios’ role in Herakles’ apotheosis. Ultimately, by focusing my interpretation of the play on Acheloios and reinforcing that interpretation with numismatic evidence, I hope to prompt others to see what a treasure the Trachiniae truly is.